Workshop Digital Marketing Dalam Mengembangkan Usaha Mikro Kecil Menengah di Gayamdompo - Fernanda, Marshanda Tiffany; Januarti, Vitalia; Kumala Sari, Vita Andarinata; Putri, Tiara Yustina; Anindyarini, Atikah (Society : Jurnal Pengabdian Masyarakat, 2022)
Group 149 of student Community Service Program from Sebelas Maret University find that there are many economic businesses in Gayamdompo. Almost all business actors, especially Small and Medium Enterprises (SMEs) are familiar with digitalization, especially in terms of marketing. To explore the details of digital marketing, business actors attended a two-day workshop with Mas Pandam as the speaker who is also the owner of Miyago Naknan. He explained how to promote products through digital media. Another speaker is Disti Fani as a creative worker explaining tips on simple product photography using gadgets. With lecture methods, discussions, counseling, and simple photography practices for SME products, the implementation of the activity have very good participation and enthusiasm from participants. Participants who attend at the Gayamdompo Village office take turns actively practicing simple photography and discussing digital marketing. After carrying out a digital marketing workshop and training on simple photography of SME products, the participants who are SME owners are expected to benefit from being able to market and promote their products better, to be able to manage SMEs more optimally and independently.